FEEDING USE OF A TROPICAL AGROECOSYSTEM (CUBA) BY MOURNING DOVE (Zenaida macroura L) - J. M. García; V. Peiró (Journal of Animal and Plant Sciences, 2016)
The Mourning dove (Zenaida macroura L.) is a species subjected to high consumptive use in Cuba, but there are a few publications related to its feeding habits in tropical regions. The goal of the present study was feeding analysis of Mourning dove to know its food spectrum, dietary importance and impact on a Caribbean agroecosystem. Seventy six samples of dove’s crop were collected in a hunting area of Cienfuegos province. The farming habitat presented higher feeding quality for this dove. The diet spectrum showed 88% plant, 9% mineral and 3% from animal origin. The seeds of Euphorbia heterphylla and Panicum maximum were the most important food items consumed by this species. Its main diet composed of 79% of seeds from herbaceous plants, with a preference for the small seeds. Crop damage caused by this dove was low, because only 10% of consumed food came from agricultural species and this dove ate seeds from plants considered weeds by farmers. Thus we concluded that this dove is a beneficial species in tropical agrosystems.
Keywords: Zenaida macroura; fullness index; food spectrum; index of dietary importance; agricultural impact